STUDI FENOMENOLOGI: PENGARUH EDUKASI TERHADAP TINGKAT KECEMASAN IBU PRIMIGRAVIDA DALAM MENGHADAPI PERSALINAN DIPMB YULI BAHRIAH KERTAPATI TAHUN 2025 - Bahriah, Yuli; Septiana, Maria; Sapitri, Ana; Anggraini, Gustika; Sapitri, Meishin (Jurnal Kesehatan Abdurrahman, 2025)
Background: Prenatal discomfort is a common psychological issue for pregnant women, especially in first pregnancies due to a lack of experience. Providing information and education is an effective way to help reduce this anxiety.Objective: This study aims to evaluate the effect of providing education on the level of anxiety in first-time pregnant women in facing the birth process in the PMB Yuli Bahriah Kertapati work area in 2025.MethodThis study used a quantitative approach with a cross-sectional analytical design. Sixty-six first-time pregnant women were selected using a simple random sampling technique. Data were collected through a questionnaire and analyzed using the Chi-Square test.Results: The research findings showed that the majority of mothers who received education experienced mild levels of anxiety (84.2%), while those who did not receive education mostly showed severe anxiety (64.3%). Statistical analysis showed a significant relationship between education provision and anxiety levels (p = 0.026).Suggestion: Health workers, especially midwives, are advised to actively provide information and maximum emotional support to first-time pregnant women to reduce anxiety leading up to childbirth. Furthermore, further research is recommended to determine the most effective educational methods.